2019
DOI: 10.48550/arxiv.1906.06919
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving Black-box Adversarial Attacks with a Transfer-based Prior

Shuyu Cheng,
Yinpeng Dong,
Tianyu Pang
et al.

Abstract: We consider the black-box adversarial setting, where the adversary has to generate adversarial perturbations without access to the target models to compute gradients. Previous methods tried to approximate the gradient either by using a transfer gradient of a surrogate white-box model, or based on the query feedback. However, these methods often suffer from low attack success rates or poor query efficiency since it is non-trivial to estimate the gradient in a high-dimensional space with limited information. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…Later, they improved the attack by drastically reducing the number of queries by focusing on estimating gradient signs instead of gradients [83]. In another attempt to decrease the number of queries, Cheng et al [85] also introduced a priorguided random gradient-free method.…”
Section: B Black-box Attacksmentioning
confidence: 99%
“…Later, they improved the attack by drastically reducing the number of queries by focusing on estimating gradient signs instead of gradients [83]. In another attempt to decrease the number of queries, Cheng et al [85] also introduced a priorguided random gradient-free method.…”
Section: B Black-box Attacksmentioning
confidence: 99%
“…This is straightforward since we can utilize {u i } q i=1 which is uniformly sampled from the (d − 1)-dimensional space H. Proposition 10. For any [9] for the proof.). Therefore,…”
Section: B54 Proof Of Lemma 12mentioning
confidence: 99%
“…We found that in this task, ARS-based methods perform comparably to RGF-based ones. Since it has been shown that PRGF with transfer-based prior works well [9], we only report the results of RGF and History-PRGF in Tab. 1, where the subscript of the method name indicates the learning rate.…”
Section: Black-box Adversarial Attacksmentioning
confidence: 99%
See 2 more Smart Citations